Emotional Regulation in Substance Uses Disorders and Their Generation - Tan Tan Davani, Hamila (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The present article focuses on emotion regulation as a predictors and treatment of substance addictions, the scope of this theoretical review is in response to the problematic issue of emotional dysregulation and its intergenerational trauma among families with substance use disorders. It is emphasized that substance dependence is a disorder characterized by a disturbance in the regulation of emotional processes. It has been found that the use of drugs in order to quickly relieve emotional pain acts as a very strong negative reinforcer and disrupts the foundations of the development of emotional management in the consumer. Of course, the children of these families do not learn emotional skills through modeling sick behavior and have difficulty in regulating and managing their emotions. Therefore, the importance of emotional skills and strengthening the management of emotions in the context of restoring emotional maturity and mental health has been investigated as one of the important tools for addiction recovery and the mental health of substance addictions and their children. In the field of emotional management psychotherapy, two classic forms of addiction treatment, which are Cognitive-behavioral therapy (CBT) and Dialectical behavior therapy (DBT), have been examined and compared. The two main known components of CBT for addiction, cognitive-behavioral therapy and functional analysis and training, are generally known to be effective in managing negative emotions. The two main known components of CBT for addiction, cognitive-behavioral therapy and functional analysis and skill training, are generally known to be effective in managing negative emotions. By analyzing specific emotional disorders among substance users' families, these emotional problems have been identified and classified, and in this regard, investigated why skills through emotion regulation therapy (ERT) is a vital part of addiction treatment.
Keywords: emotion regulation; emotion dysregulation; substance use problems; adolescents' problems; ERT; CBT; DBT